ECUACIONES PARA ESTIMAR LA FITOMASA DE Atriplex canescens - Sánchez Rigoberto, Meza (Revista Mexicana de Ciencias Forestales, 2020)
This study was carried out at the south of Saltillo in Coahuila state with the aim of obtaining dry weight estimation cqualions for tJ1e aerial biomass components of standing plants of A tri pi ex canescens. Sampling size at the site of study was of 70 plants, in each was recorded its dimensions in order to obtain 28 independent variables: after cutting and dry of the componentes. it was obtained the following dependent variables such as dry weight of sprouts (PSB), branches (PSR) and total aerial biomass (PST). The analysis of the existing relationships between dimensions and weight was performed using the logarthimic, exponencial and power lineal regression models. The criteria used for model selection was based on the highest determination coefficient, and the lowest variation coefficient. furthermore, it was considered in selecting the best equation the residual independence and the practica! use of the predictor variable. The relationships between dimensions and weight were very well explained- by the model with the following form Y a Xb ... Ei, the predictor variable was average diameter (DP) of the crown projected on the soil which was recorded considering the aritmetic mean for 4 crown diameter measurements, the obtained equations were PSB = 0.30472 (DP)1- 611365, PSR = 0.0.03405 (DP)2·44254 y PST = 0.03745 (DP)2-21993